Evaluación del posicionamiento en el motor de búsqueda Google y la necesidad de presencia en internet de las agencias de viajes y operadores turísticos de la provincia de San Martín - Barrantes Urbina, Raúl (2013)
This research was made in the province of San Martin and was conducted to travel agencies and tour operators and variables were the position in the Google search engine and internet presence need. The purpose was to find the relationship between these two variables since it is not enough having one website to have an internet presence. Also, in recent years, creating websites has increased massively, turning Google into a search engine which has the complex task of classifying and ranking millions of existing pages, It was described the Google search engine ranking based on the maturity level of the website, the level of presence in the search engine and the proficiency level and its relationship to the need for internet presence, which was determined by the interest in increasing web presence and the need to promote online services. The work was justified by having theoretical value, practical utility, and social relevance and also by the generated benefits; the type of research is applied technological, with a correlational field design that indicates the association between two variables. The population on this research was based on 18 travel agencies and tour operators. Observation method was applied and a survey was composed of 22 Likert scale items with a reliability of 0.89 with Cronbach's alpha, concluding that there's a high degree of association such that the results indicate the trend, and lower position in the Google search engine increase internet presence